Analysis of Factors Causing Employee Performance in Health Service Sector - Melan Damayanti; Andreas Wahyu Gunawan; Mutiara Sibarani Panggabean (Journal of Social Research, 2023)
People are important resources for the achievement of the vision and mission of the company's organization as a whole. HR development is the process of making employees better and better able to help a company achieve its goals. This study aims to test and analyze "Analysis of Factors Causing Employee Performance in the Healthcare Sector". The sample used in this study was 150 respondents who worked in health services. Testing was carried out using SEM analysis. The results of this study support the hypothesis that Employee Competence has a positive effect on Employee Performance, Work Motivation has a positive effect on employee performance, There is an influence of employee competence on employee performance with work motivation as an intervening variable. This research produces implicit results for owners and management of Health Services to improve Employee Performance by paying attention to and increasing Employee Competence and Work Motivation.